2020
DOI: 10.3892/ol.2020.11984
|View full text |Cite
|
Sign up to set email alerts
|

Application of the da Vinci surgical robot system in presacral nerve sheath tumor treatment

Abstract: The aim of the present study was to investigate the feasibility of da Vinci robotic surgery in the treatment of presacral tumors, and to observe its efficacy and safety. Between March 2016 and April 2019, 12 patients with presacral nerve sheath tumors underwent da Vinci robotic surgery, and the integrity of the tumor resection, surgical duration, pre-and postoperative visual analog scale (VAS) score, intra-and postoperative blood losses, postoperative bedtime, hospital stay and complications were observed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…7,8 The system has been widely used in general surgery, cardiac surgery, urology, gynecology, and other fields. [9][10][11][12] General surgery, particularly hepatobiliary and pancreatic surgery, is widely applicable in minimally invasive surgery because of its professional branches, extensive organs involved, multiple anatomical changes, and various difficult operations. In 2002, Giulianotti et al performed the first robotic hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The system has been widely used in general surgery, cardiac surgery, urology, gynecology, and other fields. [9][10][11][12] General surgery, particularly hepatobiliary and pancreatic surgery, is widely applicable in minimally invasive surgery because of its professional branches, extensive organs involved, multiple anatomical changes, and various difficult operations. In 2002, Giulianotti et al performed the first robotic hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Pu et al reported a series of 12 cases with pre-sacral nerve root tumors treated using a Da Vinci-assisted anterior approach. All patients achieved full recovery with no perioperative complications [20] . Additionally, Jun et al reported a case where a robot-assisted method was employed to resect a pre-sacral right S2 nerve root schwannoma [21] .…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, Jun et al reported a case where a robot-assisted method was employed to resect a pre-sacral right S2 nerve root schwannoma [21] . In both reports, robotic-assisted treatments showed high levels of safety, minimal blood loss, rapid recovery, and decreased length of stay [20] , [21] . In this case, utilizing Da Vinci Surgical System enabled the surgeon to perform a minimally invasive exposure of the ventral sacral roots in a small window with improved visualization, maneuverability, and suturing capability.…”
Section: Discussionmentioning
confidence: 94%
“…The DaVinci surgical robot can offer highly magnified views (up to 15 times) of the surgical area, with greater freedom of movement, which provides a guarantee for complete tumor resection, enables the operator to precisely distinguish the surrounding tissues in a narrow space and operate with more precision, thus greatly enhancing the safety of the operation [ 20 ]. A clinical study by Pu et al [ 75 ] used DaVinci surgical robot to assist in resection of tumor tissues in 12 patients with presacral nerve sheath tumors, they found that the magnified view and flexible arm of the DaVinci surgical robot allowed tumor resection to be performed with high surgical safety and accuracy, the tumors were completely removed in all 12 patients, with less intraoperative blood loss and short length of hospital stay. Additionally, the DaVinci robot has been used for the resection of thoracolumbar neurofibroma, paravertebral schwannoma, and transoral odontoidectomy [ 14 , 76 ].…”
Section: Clinical Application Scenarios For Spine Surgical Robotsmentioning
confidence: 99%